Synthesis and Characterization of Transition Metal Complexes with 1,5-Diamino 2,4-dimethyl-1,5-diaza 1,4-pentadiene - JHA, R.R.; MUKHARJEE, P. (Asian Journal of Chemistry, 2010)
Metal complexes of the type [M3(DDDP)2X6(H2O)4] [where M = Mn2+, Co2+ and Ni2+, DDDP = 1,5-diamino 2,4-dimethyl 1,5-diaza 1,4-pentadiene, X = Cl-, NO-3 and ClO-4] have been synthesized in neutral medium. The ligand is coordinated to metal ion through azomethine nitrogen as indicated from IR spectra. Octahedral geometry has been proposed for the complexes on the basis of magnetic susceptibility and electronic spectral study. Thermal analysis of all the complexes shows similar pattern of decomposition. Weight loss takes place in one step, 175°C with exothermal peak in D.T.A. curve which corresponds to loss of four water molecules which shows that water molecuels are coordinated to metal ions. Fungicidal screening of the complexes shows them active against Aspergillus niger, Fusarium orysporium and Helminthosporium oryzae. These complexes are less active than the thio complexes.